Molecular Typing of Blood Cell Antigens - Bugert, Peter.; Bugert, Peter. (Methods in Molecular Biology,, 2015)
This volume aims to bring together a variety of protocols useful for DNA-based typing of blood cell antigens. Protocols range from simple approaches with low technical complexity to highly sophisticated modern developments. Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Molecular Typing of Blood Cell Antigens summarizes contributions from leading scientist in the field DNA typing for blood cell antigens.